2002
DOI: 10.1359/jbmr.2002.17.4.734
|View full text |Cite
|
Sign up to set email alerts
|

Universal Standardization of Forearm Bone Densitometry

Abstract: As part of an effort to quantify device-dependent differences in forearm bone density, 101 women, aged 20 -80 years (ϳ16 women in each age decade), were scanned on six forearm bone densitometers: the Aloka DCS-600EX, the Hologic QDR-4500A, the Lunar PIXI, the Norland pDEXA, the Osteometer DTX-200, and the Pronosco X-posure System. Regression statistics are reported for all similar regions of interest (ROIs). However, comparisons were confounded because of large differences in the ROI size and placement. The nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 18 publications
4
22
2
Order By: Relevance
“…This concurs with our Bland-Altman, cross-classification analysis and kappa statistics, which all demonstrated that the PIXI BMD was in greatest agreement with the DXA UD forearm BMD. These results in young children are similar to previous results in adults, which demonstrated agreement between PIXI and DXA forearm BMD (12).…”
Section: Discussionsupporting
confidence: 91%
“…This concurs with our Bland-Altman, cross-classification analysis and kappa statistics, which all demonstrated that the PIXI BMD was in greatest agreement with the DXA UD forearm BMD. These results in young children are similar to previous results in adults, which demonstrated agreement between PIXI and DXA forearm BMD (12).…”
Section: Discussionsupporting
confidence: 91%
“…Our comparison used a diverse population of pediatric and adults, males and females, with mixed ethnicities, and two clinical sites. Previous universal standardization studies (1,11,15) were performed using one densitometry system from each manufacturer and for only women.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the final sample size was 57.4% (271/ 472), and the present findings may not be applicable to frail older people who have low physical functional capacity where BMD at the hip could not be measured in the prone position. Second, BMD has been measured at virtually all available measurement sites (spine, proximal femur, forearm, whole body, calcaneus, and tibia) [40,41]. In the present study, only the proximal femur, i.e., the femoral neck and trochanter regions, was used as an indicator of all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%